A clinical study of various presentations of intestinal tuberculosis, evaluation, management and its complications - Basa, Maruti; Prakash, Karnati (International Surgery Journal, 2020)
Background: Abdominal tuberculosis includes tuberculous infection of gastrointestinal tract, mesentery, lymph nodes and omentum, peritoneum and solid organs like liver and spleen. The initial clinical presentations are nonspecific and no single laboratory investigation is pathognomonic. Bacterial culture and tissue histopathology though confirmatory are time consuming, and immunological tests though rewarding is expensive. Moreover, abdominal tuberculosis with an acute abdomen presents as an enormous challenge to the surgeon. Methods: This one-year prospective observational study of 25 patients who presented with intestinal tuberculosis at the Department of General Surgery, NIMRA Medical College from February 2019 to January 2020. The causes of intestinal tuberculosis were determined along with clinical profile and were monitored for outcome based on the morbidity and mortality. Results: Among the 25 patients, all had intestinal tuberculosis on the basis of operative findings and histopatholoigcal reports. Age of the patients ranged between 9 to 70 years; majority (75%) were in the age group of 20 to 40 years. Female to male ratio was 1.7:1. The commonest operative findings were hyperplastic ileocaecal tuberculosis (16%), followed by strictures (20%), and perforations (24%). The overall mortality was 8% due to sepsis and septic shock. Conclusions: Intestinal tuberculosis is a common problem presenting to general surgical units in the developing countries, often in an acute form. A high index of suspicion, proper evaluation and therapeutic trial in suspected patients is essential for an early diagnosis, in order to minimize complications.